Study of the Socio-Demographic Profile, Pattern of Substance Abuse and Criminal Behaviour in Patients with Opioid Use Disorder - Yadav , R; Rai , RK; Kumar, DS; Singh , VK; Singh , AP; Kaul, A (Journal of Indian Academy of Forensic Medicine, 2024)
With the ongoing increase in supply, temptations, stressful lifestyle and easy availability, substance abuse is growing amongst different  populations at an alarming rate. Its demand is increasing alarmingly in the younger generation due to various socio-economical reasons.  Substance abuse has also been found to be associated with violent behaviour and infectious diseases. The aims of this study were to find  out the socio-demographic profile, pattern of substance abuse and criminal behaviour associated with Opioid Use Disorder. 106 diagnosed  patients of Opioid Use Disorder registered at the OSTCentre, Department of Psychiatry, S.R.N. Hospital, associated with Moti Lal Nehru  Medical College, Prayagraj were included. All patients were interviewed according to a semi-structured questionnaire prepared for the  purpose of collection of information regarding patterns of opioid abuse and history of criminal behaviour, if any. Out of 106 cases, 48 were  found with a history of criminal behaviour. Criminal behaviour was found mostly amongst the cases of unemployed and uneducated cases.  Cannabis was found to be the most common substance used prior to initiation of opioid abuse. The 20-29 years age group was found to be  the most vulnerable age group for initiation of opioid abuse and commission of crime. Accordingly, the 2nd and 3rd decade of life needs  better familial and social support along with strict law enforcement related to the supply of illicit substances.
Keywords: Opioid addiction; Criminal behaviour; Criminality; Alcohol; Cannabis.